Recent Plant Traits of Caulerpa taxifolia var. distichophylla in the Turkish Aegean Sea - Erhan Mutlu; Barış Akçalı; Yaşar Özvarol; Zeynep Narlı; Berivan Elif Aslan; Zeynep Zabun (Aquatic Sciences and Engineering)
A research cruise was conducted along the Turkish coast of the Aegean Sea between May and August 2024 to assess the distribution and plant characteristics of Caulerpa taxifolia var. distichophylla. During the survey, samples of Caulerpa taxifolia var. distichophylla were identified at one station in August 2024 in Tatlısu Gulf, Altınova Bay, Balıkesir among 321 stations. Specimens were collected from one station located at a depth of 20 m. The density of shoots was estimated to be 344 m-2. Morphological analyses revealed that the specimens were characterized by a light green, delicate, feathery thallus with thin prostrate stolons and erect fronds with pinnae. The erect fronds ranged in height from 2.10 mm to 105 mm, with a mean of 46.51 ± 1.4 mm, and in width from 1.30 mm to 4.10 mm, with a mean of 2.68 ± 0.003 mm. A significant relationship was found between the number of pinnae and frond length, with a slope of approximately 2.15. The relationship between frond length and width followed a curved-linear (logarithmic) model, with a slope of approximately 0.515. This study provides the latest comprehensive biometric data on C. taxifolia var. distichophylla, which has spread to the north of the Turkish Aegean Sea after its in the Gulf of Izmir in 2011, and contributes to the understanding of its invasive potential and ecological impacts in the region.